Managing Clutter in a High Pulse Rate Echolocation System - Isbell, Jacob; Horiuchi, Timothy K. (Frontiers in Neuroscience, 2018)
The use of echolocation for navigating in dense, cluttered environments is a challenge due to the need for rapid sampling of nearby objects in the face of delayed echoes from distant objects. In the wild, echolocating bats frequently encounter this situation when leaving the roost or while hunting. If long-delay echoes from a distant object are received after the next pulse is sent out, these “aliased” echoes appear as close-range phantom objects. Little is known about how bats cope with these situations. In this work, we demonstrate a novel strategy to manage aliasing in cases where a single target is actively being tracked at close range. This paper presents three reactive strategies for a high pulse-rate sonar system to combat aliased echoes: 1) changing the interpulse interval to move the aliased echoes away in time from the tracked target, 2) changing positions to create a geometry without aliasing, and 3) a phase-based, transmission beam-shaping strategy to illuminate the target and not the aliasing object.